2015
DOI: 10.3389/fphys.2015.00399
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Exercise Training Improves Skeletal Muscle Regeneration Potential

Abstract: Purpose: The aim of this study was to determine whether 12 days of low-to-moderate exercise training at low altitude (598 m a.s.l.) improves skeletal muscle regeneration in sedentary adult women.Methods: Satellite cells were obtained from the vastus lateralis skeletal muscle of seven women before and after this exercise training at low altitude. They were investigated for differentiation aspects, superoxide anion production, antioxidant enzymes, mitochondrial potential variation after a depolarizing insult, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…In skeletal muscle, AET reduces inflammation, oxidative stress, and energy metabolism and improves the balance between muscle protein synthesis and degradation . Moreover, there are data supporting the notion that AET can increase and/or decrease skeletal muscle myomiRs and, in consequence, alter skeletal muscle phenotype in cardiovascular diseases …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In skeletal muscle, AET reduces inflammation, oxidative stress, and energy metabolism and improves the balance between muscle protein synthesis and degradation . Moreover, there are data supporting the notion that AET can increase and/or decrease skeletal muscle myomiRs and, in consequence, alter skeletal muscle phenotype in cardiovascular diseases …”
Section: Introductionmentioning
confidence: 96%
“…3,5,26,27 Moreover, there are data supporting the notion that AET can increase and/or decrease skeletal muscle myomiRs and, in consequence, alter skeletal muscle phenotype in cardiovascular diseases. [28][29][30][31][32] Previous studies show that inspiratory muscle training (IMT) decreases sympathetic nerve activity and improves muscle blood flow and functional capacity in patients with HFrEF. [33][34][35][36][37][38][39] However, the effects of IMT on skeletal muscle myopathy in patients with HFrEF remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that miR-1 and miR-133 expression significantly increased in marathon athletes after exercise (Gomes et al, 2014). However, another study demonstrated that miR-1 and miR-133 expression was significantly downregulated after exercise (Pietrangelo et al, 2015). These paradoxical results may be attributed to individual variations and differences in exercise duration.…”
Section: Mir-1 and Mir-133mentioning
confidence: 99%
“…Reactive oxygen species are chemically reactive molecules containing oxygen with an unpaired electron and this conformation gives them the possibility to interact with different other molecules (28). These molecules are considered regulators of cellular functions during inflammatory response, but an over-accumulation beyond a certain threshold, can have different detrimental effects (29). ROS activity can last for days in absence of an adequate antioxidant response and these species can move outside the cell and react with other tissues provoking oxidative stress (30).…”
Section: Etiology Of Sarcopenia and Cancer Cachexiamentioning
confidence: 99%